Delayed pubarche - Francesco Baldo; Egidio Barbi; Gianluca Tornese (BMC, 2021)
Abstract In healthy adolescents, delayed pubarche is generally a benign condition that is caused by a physiological discrepancy between gonadarche and adrenarche. In presence of other clinical signs and symptoms, delayed pubarche can be caused by single or multiple hormones deficiency (such as adrenal insufficiency, panhypopituitarism and hypothyroidism) and/or genetic conditions (Turner syndrome, androgen insensitivity syndrome). Exposition to endocrine disruptors has also been described as a possible cause of delay of pubic hair development. Basic blood tests, karyotype and first level imaging studies are helpful in the differential diagnosis.